Water Hyacinth (Eichhornia crassipes) a challenge for water body management - Seswoya, Roslinda; Hong Siew Yi (Recent Trends in Civil Engineering and Built Environment, 2020)
Water hyacinth is one of invasive aquatic plant, and grow abundantly in water body. The water body conditions and water hyacinth reproductive mechanism are the main reasons for its rapid growth. The excess of water hyacinth in the water body not only affecting the water quality but also threatening the biodiversity. The machinery is used to remove the water hyacinth from the water body. Unfortunately is budget tight and burden the appropriate authority. Water hyacinth is a biomass which is high in moisture content and carbon to nitrogen ratio, indicating that the anaerobic digestion is preferable for the biomass stabilization. Few studies had proved that the water hyacinth is anaerobically digested and resulted in the methane yield up to 190 ml CH4/g Vs.